2018
DOI: 10.31139/chnriop.2018.83.5.35
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of complications resulting from femoral neck fracture treatment using Targon FN system

Abstract: The study was aimed to assess the outcomes of the operative procedure applied in the patients with the femoral neck fracture, treated with the Targon FN system, manufactured by Aesculap, and identify relationships between the outcome of treatment of the femoral neck fracture, patient's body mass, length of the period between the moment of injury and surgery, age of patient, prescribed medications. Study criteria were met by 19 patients aged between 25 and 87 and the average follow-up time was 20 months. Over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…This was revealed by a study by Jan Poszepczyński et al from Poland to identify relationships between the outcome of femur neck fracture treated with the Targon FN system manufactured by Aesculap, patient's body mass, length of the period between the moment of injury and surgery, age, and prescribed medications. 17 They confirmed that the most serious complications occurred in patients who had a postponed surgery, i.e., over 4 days after injury involving a 31B3 fracture and no relationship between the outcome of treatment and the patient's age, body mass or received medications. The best results of treatment were obtained in the patients operated on the first or second day after injury.…”
Section: Discussionmentioning
confidence: 86%
“…This was revealed by a study by Jan Poszepczyński et al from Poland to identify relationships between the outcome of femur neck fracture treated with the Targon FN system manufactured by Aesculap, patient's body mass, length of the period between the moment of injury and surgery, age, and prescribed medications. 17 They confirmed that the most serious complications occurred in patients who had a postponed surgery, i.e., over 4 days after injury involving a 31B3 fracture and no relationship between the outcome of treatment and the patient's age, body mass or received medications. The best results of treatment were obtained in the patients operated on the first or second day after injury.…”
Section: Discussionmentioning
confidence: 86%